2015
DOI: 10.3989/gya.0711142
|View full text |Cite
|
Sign up to set email alerts
|

Quality parameters of olive oil from stoned and nonstoned Koroneiki and Megaritiki Greek olive varieties at different maturity levels

Abstract: SUMMARY:Virgin olive oil is a natural functional food and its beneficial role in health as an integral ingredient of the Mediterranean diet is universally recognized. The effects of olive pitting, degree of ripeness and variety (Greek varieties Koroneiki and Megaritiki) were investigated on the physicochemical characteristics, antioxidant constituent contents and capacity and on the fatty acid profile of olive oil. Ripeness resulted in a decrease (P<0.05) in phenolic and tocopherol contents and the unsaturated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…According to studies carried out by Buffa, Tropea, Mattar, Carelli, & Ceci (2013) and Katsoyannos et al (2015), as the RI of olives increases, the relationship between percentages of oleic/linoleic acid found in the oil decreases. This trend agrees with the results obtained in this study for both harvest years, as shown in Table 2.…”
Section: Fatty Acid Compositionmentioning
confidence: 96%
See 3 more Smart Citations
“…According to studies carried out by Buffa, Tropea, Mattar, Carelli, & Ceci (2013) and Katsoyannos et al (2015), as the RI of olives increases, the relationship between percentages of oleic/linoleic acid found in the oil decreases. This trend agrees with the results obtained in this study for both harvest years, as shown in Table 2.…”
Section: Fatty Acid Compositionmentioning
confidence: 96%
“…According to Katsoyannos et al (2015), as the ripeness index increases, the total contents of tocopherols and polyphenols decrease. This was not observed in the present study, as the RI did not significantly affect (p > 0.05) the polyphenol content in either harvest year evaluated.…”
Section: Polyphenolsmentioning
confidence: 99%
See 2 more Smart Citations
“…Complementary oxidative stability indices such as K 232 and K 268 values represent the presence of conjugated diene and triene compounds, respectively (AOCS, 1998;Katsoyannos et al, 2015). The K 232 values of the samples were increased by prolonged storage periods (Figure 2a).…”
Section: K 232 and K 268 Valuesmentioning
confidence: 99%